2001
DOI: 10.1023/a:1011928723070
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We use a nonsteady-state model to evaluate the effects of community adaptation and sorption kinetics on the fate of linear alkylbenzene sulfonate (LAS) in batch experiments conducted with activated sludge that was continuously fed different concentrations of LAS. We observed a sharp decrease in the biodegradation rate between 30 and 60 minutes and the presence of an LAS residual at the end of the batch experiments. The modeling analysis indicates that these phenomena were caused by relatively slow inter-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The importance of sludge adaptation and mass transfer in the biodegradation process of LAS in activated sludge treatment was studied [55].…”
Section: Biodegradation Of Linear Alkylbenzene Sulfonate (Las)mentioning
confidence: 99%
“…The importance of sludge adaptation and mass transfer in the biodegradation process of LAS in activated sludge treatment was studied [55].…”
Section: Biodegradation Of Linear Alkylbenzene Sulfonate (Las)mentioning
confidence: 99%
“…The importance of sludge adaptation and mass transfer in the biodegradation process of LAS in activated sludge treatment was studied [55]. A model was developed to analyze the effects of adsorption and biodegradation kinetics on the fate of LAS in batch experiments with activated sludge adapted to different initial LAS concentrations.…”
Section: Biodegradation Of Linear Alkylbenzene Sulfonate (Las)mentioning
confidence: 99%
“…LAS has also shown inhibitory effects on the anaerobic biological treatment [7,8]. It has been reported that LAS with the concentrations of less than 10 mg/L is biodegradable under aerobic activated sludge treatment and its degradation follows Monod's equation over the ranges of 0.1-20 mg/L [9]. Moreover, it has been reported that the fate of LAS can follow first order kinetics for the similar ranges of concentrations [10].…”
Section: Introductionmentioning
confidence: 99%